2018
DOI: 10.1038/s41598-018-25333-8
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus fermentum strain JDFM216 stimulates the longevity and immune response of Caenorhabditis elegans through a nuclear hormone receptor

Abstract: Here, we examined the functionality of Lactobacillus fermentum strain JDFM216, a newly isolated probiotic bacterium, using a Caenorhabditis elegans model. We determined bacterial colonization in the intestinal tract of C. elegans by plate counting and transmission electron microscopy and examined the survival of C. elegans using a solid killing assay. In addition, we employed DNA microarray analysis, quantitative real time-polymerase chain reaction, and immunoblotting assays to explore health-promoting pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 42 publications
(56 reference statements)
4
81
0
Order By: Relevance
“…Both live E. coli and LAB can colonize in worms (Berg et al, 2016; Chelliah et al, 2018; Park et al, 2018; Portal-Celhay, Bradley, & Blaser, 2012). Live bacteria are necessary for some physiological roles; secreted enterobactin from live E. coli in the gut promotes C. elegans growth (Qi & Han, 2018); live, but not dead, LAB reduced the susceptibility to pathogenic bacteria Pseudomonas aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both live E. coli and LAB can colonize in worms (Berg et al, 2016; Chelliah et al, 2018; Park et al, 2018; Portal-Celhay, Bradley, & Blaser, 2012). Live bacteria are necessary for some physiological roles; secreted enterobactin from live E. coli in the gut promotes C. elegans growth (Qi & Han, 2018); live, but not dead, LAB reduced the susceptibility to pathogenic bacteria Pseudomonas aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…The PMK-1 pathway is also activated by Lb. acidophilus and Lactobacillus fermentum (Kim & Mylonakis, 2012; Park et al, 2018). Worms fed a lactic acid bacteria, Weissella , show higher expression of daf-16, aak-2 , and jnk-1 , and extend lifespan in these genes-dependent manners (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We choose C. elegans as a relevant in vivo model for studying the pathogenicity of microorganisms [21,[28][29][30][31] and the antimicrobial properties of lactic acid bacteria [32,33]. Unlike in vitro experiments which demonstrated no significant antifungal effects of the LBM, those performed in vivo showed that Lcr35 ® had interesting curative anti-C. albicans properties in the nematode.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes occur rather by triggering the p38 MAPK pathway, which culminates with the nuclear translocation of the transcriptional factor skinhead family member (SKN)-1 [9]. SKN-1, an ortholog of the mammalian Nrf2, induces the expression of target genes involved in oxidative stress resistance and it is responsible for the beneficial effect exerted by several other probiotic microbes [37,62,69].…”
Section: Mechanisms Involved In C Elegans Lifespan Extension Indumentioning
confidence: 99%